2010
DOI: 10.14742/ajet.1094
|View full text |Cite
|
Sign up to set email alerts
|

Domestication of a laptop on a wireless university campus: A case study

Abstract: This study reports how university students domesticate their personal laptops at the beginning of studies on a wireless campus. The aim was to examine how students integrate the laptop into their personal education experience, what sort of processes were experienced to render the laptop useful and meaningful, and how gender and IT proficiency influenced this process. Qualitative interview data with twenty students (identified and selected by quantitative survey) was analysed using the grounded theory approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 24 publications
(17 reference statements)
0
15
0
3
Order By: Relevance
“…They determined that proposing a single learning model for all disciplines is not optimal; it should be the subject matter of the courses that determines how best to integrate the technology. Furthermore, Vuojärvi, Isomäki, and Hynes (2010) explored the relative ease/difficulty that students in laptop mandated programs had in integrating the laptop into their personal and academic lives; they found that students who had a higher proficiency with information technology, and especially those who had prior experience with the software used in class, were quicker to adopt the laptop as both a learning tool and a personal tool. However, our focus was on the integration of tablet technology.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They determined that proposing a single learning model for all disciplines is not optimal; it should be the subject matter of the courses that determines how best to integrate the technology. Furthermore, Vuojärvi, Isomäki, and Hynes (2010) explored the relative ease/difficulty that students in laptop mandated programs had in integrating the laptop into their personal and academic lives; they found that students who had a higher proficiency with information technology, and especially those who had prior experience with the software used in class, were quicker to adopt the laptop as both a learning tool and a personal tool. However, our focus was on the integration of tablet technology.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lauricella and Kay (2010) reported that students perceived the laptops to be helpful for many academic tasks including note-taking and organization which assisted their academic progress. Vuojärvi, Isomäki, and Hynes (2010) explored how students in laptop-mandated programs integrated the laptop into their personal and academic lives, finding that students who had a higher proficiency with information technology, and especially those who had prior experience with the software used in their classes more easily adopted the laptop as a learning tool.…”
Section: Student Perception Of In--class Use Of Technologymentioning
confidence: 99%
“…The teenagers were now ICT specialists and would invite their friends for some computer literacy lessons. Vuojärvi, Isomäki, and Hynes (2010) suggest that "successful domestication comes about when the technology is successfully embedded within the daily routine and habits" (p. 261). The diversity in the number of activities that the members of Household 18 were involved in provides the evidence of successful domestication of the ICT resources.…”
Section: Incorporationmentioning
confidence: 99%